1999
DOI: 10.1177/0739986399213009
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Circumstances of Child Sexual Abuse among Latina Women

Abstract: This study examined the prevalence and circumstances of child sexual abuse in a community sample of Latina women, 18 to 50 years of age. Chi-square tests of independence and t-test procedures were used to assess the prevalence, characteristics of the victim, assault, perpetrator, disclosure, and long-term effects. One in three Latina women reported incidents of sexual abuse, regardless of acculturation or citizenship status. More than one third of the women also experienced revictimization, with more than 80% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
24
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 18 publications
(28 reference statements)
13
24
0
Order By: Relevance
“…Neither permanent legal status nor feminine gender role had any significant effects on formal or informal help-seeking. The findings support the existing literature by showing that low levels of acculturation serve as a hindrance to formal help-seeking (Cortina 2004;Lipsky et al 2006;Romero et al 1999;Wells et al 1987;West et al 1998). It is likely that Anglo acculturation, as it is largely based on language preference, increases access to formal services because of a better command of the English language.…”
Section: Discussionsupporting
confidence: 85%
“…Neither permanent legal status nor feminine gender role had any significant effects on formal or informal help-seeking. The findings support the existing literature by showing that low levels of acculturation serve as a hindrance to formal help-seeking (Cortina 2004;Lipsky et al 2006;Romero et al 1999;Wells et al 1987;West et al 1998). It is likely that Anglo acculturation, as it is largely based on language preference, increases access to formal services because of a better command of the English language.…”
Section: Discussionsupporting
confidence: 85%
“…National data concerning CSA rates among Latino women, using adult retrospective studies, present rates that range between 15.4% and 32.1% depending on the criteria that are used to define CSA (Vogeltanz et al, 1999). In some college sample studies that have focused specifically on Latino women (Clemmons et al, 2003) or compared them to their non-Latino counterparts (Arroyo et al, 1997;Clemmons et al, 2003;Kalof, 2000;Romero, Wyatt, Loeb, Carmona, & Solis, 1999;Ullman & Filipas, 2005;Urquiza & Goodlin-Jones, 1994;Vera et al, 2005) reported rates of CSA ranged between 26% and 38%, which is consistent with CSA rates from community samples (Ulibarri, Ulloa, & Camacho, 2009). Due to methodological variation and definitional discrepancies, CSA rates among Latino women are very disparate.…”
Section: Sexual Victimizationsupporting
confidence: 49%
“…In addition, Kaslow and her colleagues (Kaslow et al, 1998(Kaslow et al, , 2000 have found that both CSA and partner abuse were significantly associated with suicide attempts in African American women. Few studies have specifically examined factors associated with CSA in Latina samples, but Romero and Wyatt (1999) observed that there are specific issues affecting Latina women, such as a tendency toward nondisclosure, and emphasized the need for further research addressing these issues. The present study adds to this literature by demonstrating the pronounced impact of CSA on decisions to remain in an abusive relationship within a multiethnic sample.…”
Section: Discussionmentioning
confidence: 99%